2021
DOI: 10.1093/nar/gkab244
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylases control lysine acetylation of ribosomal proteins in rice

Abstract: Lysine acetylation (Kac) is well known to occur in histones for chromatin function and epigenetic regulation. In addition to histones, Kac is also detected in a large number of proteins with diverse biological functions. However, Kac function and regulatory mechanism for most proteins are unclear. In this work, we studied mutation effects of rice genes encoding cytoplasm-localized histone deacetylases (HDAC) on protein acetylome and found that the HDAC protein HDA714 was a major deacetylase of the rice non-his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 86 publications
3
47
0
Order By: Relevance
“…However, it has been shown that post translational modifications such as the ubiquitylation and phosphorylation of ribosomal proteins may have functional effects on translational control (39). A more recent study demonstrated that Kac is an important post translational modification of R-proteins that reduces R-protein stability and may increase the combinatorial diversity of ribosome activities (40). The data obtained in this work showed that 30% of total ribosomal proteins were acetylated (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…However, it has been shown that post translational modifications such as the ubiquitylation and phosphorylation of ribosomal proteins may have functional effects on translational control (39). A more recent study demonstrated that Kac is an important post translational modification of R-proteins that reduces R-protein stability and may increase the combinatorial diversity of ribosome activities (40). The data obtained in this work showed that 30% of total ribosomal proteins were acetylated (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…It should be emphasized that genetic improvement is the most important way to improve rice quality [104][105][106]. In recent years, a number of good-quality rice varieties or lines have been bred through molecular breeding technologies such as transgenic and gene-editing [106][107][108]. Further studies are needed to breed rice varieties or lines with a high content of amino acids, especially essential amino acids such as Lys, in the ripe grains though genetically optimizing the spatial and temporal distributions of the content and compositions of amino acids in the grain during the filling.…”
Section: Regulation Techniques For Promoting Biosynthesis Of Amino Ac...mentioning
confidence: 99%
“…This suggests that LysAc is probably necessary for the regulation of protein synthesis and assembly. A KDAC (HDA714) has been shown to target RPs for LysDeAc, which is likely to affect the stability of the ribosome and its translational efficiency ( Xu et al., 2021 ). However, rare homologous Lys-acetylated HSPs or conserved Lys-acetylated sites have been found in the current study.…”
Section: Characteristics Of Lys-acetylated Proteinsmentioning
confidence: 99%